2012
DOI: 10.1371/journal.pone.0049098
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses in Relation to Performance during Competition in Elite Synchronized Swimmers

Abstract: PurposeWe aimed to characterize the cardiovascular, lactate and perceived exertion responses in relation to performance during competition in junior and senior elite synchronized swimmers.Methods34 high level senior (21.4±3.6 years) and junior (15.9±1.0) synchronized swimmers were monitored while performing a total of 96 routines during an official national championship in the technical and free solo, duet and team competitive programs. Heart rate was continuously monitored. Peak blood lactate was obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
74
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(90 citation statements)
references
References 53 publications
15
74
0
1
Order By: Relevance
“…Arterial oxygen desaturation occurred more quickly in trained divers during maximal dynamic breath-hold dives compared with static dives and, as expected, the postdive lactate increase was greater for the combination of apnea and dynamic exercise (7). Other studies have shown a relationship between the bradycardic response or arterial oxygen desaturation and performance in elite synchronized swimmers, divers, and underwater hockey players (7,14,18,22).…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Arterial oxygen desaturation occurred more quickly in trained divers during maximal dynamic breath-hold dives compared with static dives and, as expected, the postdive lactate increase was greater for the combination of apnea and dynamic exercise (7). Other studies have shown a relationship between the bradycardic response or arterial oxygen desaturation and performance in elite synchronized swimmers, divers, and underwater hockey players (7,14,18,22).…”
Section: Introductionsupporting
confidence: 58%
“…It was found that the divinginduced bradycardia during moderate dynamic cycle exercise was powerful (7) enough to override the exercise tachycardia for the period of apnea (1)(2)(3)(4)24). However, more recent studies in elite synchronized swimmers (22) and trained breath-hold divers (17) showed that with higher exercise intensity, HR was increased during dynamic apnea compared with dry static apnea, but a relative bradycardic response was still observed during the dynamic apnea. Arterial oxygen desaturation occurred more quickly in trained divers during maximal dynamic breath-hold dives compared with static dives and, as expected, the postdive lactate increase was greater for the combination of apnea and dynamic exercise (7).…”
Section: Introductionmentioning
confidence: 99%
“…Although bioelectrical variables are normalized for height, BMI calculation enables better contextualization of the sample. The results of the BMI in both groups (Table 1)—underweight and normal weight in C o and J r swimmers, respectively—seem to be coherent with the great physiological demands of this sport [4]. These anthropometric characteristics are necessary to understand that the bioelectrical signal will also be specifically related to each sport, sex and age [15].…”
Section: Discussionmentioning
confidence: 97%
“…Some previous studies have discovered presence of a weakened ventilation response in breath-hold divers and synchronized swimmers (2,4,10,33). However, the hypothesis that exposure to hypercapnic condition reduces the ventilation response to increased CO2 concentrations was rejected.…”
Section: Introductionmentioning
confidence: 99%